PENGARUH PENERAPAN STRATEGI CSR (CORPORATE SOCIAL RESPONSIBILITY) DALAM MENINGKATKAN CITRA PERUSAHAAN PADA PT. PERTAMINA (PERSERO) TAHUN 2018 - Dina Anggresa Oktina; Eka Septiana Sari; Intan Angelina Intan Angelina Sunardi; Laili Nurul Hanifah; Vicky F Sanjaya (Kompetensi (Competence : Journal of Management Studies), 2020)
The purpose of this research to determine the effect of implementing the CSR strategy carried out by PT. Pertamina (Persero) through various programs owned by the company's image. The method used in this research is a qualitative method/ approach. This research was made not to test the hypothesis between the two variables, but to describe the extent of CSR programs that have been run by PT. Pertamina (Persero) can play  a  role  in  improving  the  company's  image.  The  data collected is data obtained from the annual report of PT. Pertamina (Persero) in 2018 taken from IDX, articles and other documents. Data analysis techniques used in this study use comparative  analysis  (comparing  the  findings  of  researchers with the theory used) and include data reduction, data presentation and drawing conclusions. Based on the results of the analysis of the data obtained, the strategy embodied in the CSR program of PT. Pertamina (Persero) has been carried out in accordance with the company's vision, mission, principles and strategy set by the company itself. The results obtained from this study indicate that the overall implementation of CSR strategies carried out by PT. Pertamina (Persero) basically has an influence and plays an active role in improving the image, reputation and credibility of the company. In this case, things that must be done by PT. Pertamina (Persero) is considering expanding the scope of the area of the recipients of the CSR programs they have, so that not only the people in the vicinity of the head office or its subsidiaries can benefit from each CSR program that is carried out, but also the community as a whole.